Shifting the Dialog, Shifting the Culture : Pathways to Successful Postsecondary Outcomes for Deaf Individuals. - Cawthon, Stephanie W. (Deaf Education Ser., 2017)
"In this volume, Stephanie W. Cawthon and Carrie Lou Garberoglio discuss the individual and systemic factors that both facilitate and inhibit the attainment of postsecondary education, training, and career goals for deaf individuals. Real-life examples and current research are combined in this consideration of the interactions between individuals and the many layers of the overall system in which they navigate. In addition to using a systems theory approach, the authors employ resiliency models that emphasize how deaf individuals persist through the transition process amidst the barriers that reside within larger educational and social systems. Employment, independent living, and community involvement are a few of the postsecondary outcomes that are covered. Shifting the Dialog, Shifting the Culture addresses critical issues that influence how deaf individuals reach their postsecondary goals and is designed for a diverse audience that includes professionals who work (or are training to work) with deaf individuals, policy makers, as well as federal and state personnel."